Design and Development of a Pine Needle Briquetting Machine for the Uttarakhand Region of India - Tejas Pramod Naik; Soumyajeet Jaiswal; Inderdeep Singh; Apurbba Kumar Sharma; Ayush Joshi (Mechanics of Advanced Composite Structures)
Fossil fuels, a non-renewable source, supply more than 81% of the world’s primary energy and contribute heavily to global climate change. This paper represents a strategy to address the administration of forest bio residue in the northern Himalayan district of India. Uttarakhand state, the north part of India, is rich in bio residues such as Pine needles of Chir Pine (Pinus roxburghii). Every year during the summer, there is a forest fire breakout, mainly caused by these dry pine needles, which cover a forest floor and are highly flammable. This forest bio residue is renewable and is a potential energy source for rural livelihoods, which would also generate social business enterprises among the locals. This is an effort to develop a practical manual-operated briquetting machine (BM) capable of fabricating briquettes from forest waste. The primary materials utilized to make briquettes are pine needles and forest waste. The proposed method inculcates principles of compression molding along with necessary optimizations. Briquetting is one of the cheapest ways to harvest the destructive energy of pine needles in a clean and economically viable way. Briquetting machines reduce forest fires by reducing dependency on wood from forests for fuel while simultaneously lowering carbon emissions by using biomass or agricultural waste as alternative fuel sources. This dual benefit protects forests and helps battle climate change and local air pollution, making it a long-term option for environmental protection. The developed BM is one solution that can solve the dual purpose of climate change mitigation and employment. The designed and developed machine fabricates thirty-three briquettes per hour and is currently installed in the Uttarkashi district of Uttarakhand, India.